Death-associated protein 3 in cancer—discrepant roles of DAP3 in tumours and molecular mechanisms - Song, Hao; Liu, Huifang; Wang, Xiufeng; Yang, Yuteng; Zhao, Xiangkun; Jiang, Wen G.; Sui, Laijian; Song, Xicheng (Frontiers in Oncology, 2024)
The article has a word count of 4657 as well as contains an image and a table Abstract: Cancer, ranks as the secondary cause of death, is a group of diseases that are characterized by uncontrolled tumor growth and distant metastasis, leading to increased mortality year-on-year. To date, targeted therapy to intercept the aberrant proliferation and invasion is crucial for clinical anticancer treatment, however, mutant expression of target genes often leads to drug resistance. Therefore, it is essential to identify more molecules that can be targeted to facilitate combined therapy. Previous studies showed that death associated protein 3 (DAP3) exerts a pivotal role in regulating apoptosis signaling of tumors, meanwhile, aberrant DAP3 expression is associated with the tumorigenesis and disease progression of various cancers. This review provides an overview of the molecule structure of DAP3 and the discrepant roles played by DAP3 in various types of tumors.Considering the molecular mechanism of DAP3-regulated cancer development, new potential treatment strategies might be developed in the future.